Interactive effects of corporate social responsibility and other value-creating investments on corporate financial performance. (2016) - Wang, Xiaodan; Feng, Mingming; Palmer, Timothy B.
Research on the financial benefits of corporate social responsibility (CSR) has proliferated in recent years but generated mixed results. Rather than asking if CSR helps or hinders firm performance, it might be more worthwhile to explore conditions impacting relations between CSR and firm performance. That is, given the potential trade-offs between investments in CSR and those in other value-creating activities, it is necessary to examine their interactive impacts on corporate financial performance (CFP). Toward this end, this study explores if, and how, investments in innovation capabilities, branding capabilities and managerial capabilities moderate the effect of CSR on CFP. Testing the hypotheses with a sample of 579 US firms from 1991 to 2010, we found that the positive effect of CSR on CFP is weaker in firms that are more innovative and better at branding, and stronger in firms that spend more on acquiring managerial capabilities.